2020
DOI: 10.1111/oik.07435
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of European ungulate dietary studies: a synthesis

Abstract: Over recent decades, ungulate populations across Europe have undergone a rapid recovery. While this constitutes a conservation success, there is increasing concern about their impacts on shared resources with humans. Understanding ungulate food choices is crucial for predicting such impacts. Numerous studies have focused on single species or communities at narrow spatial scales. Here, we used 265 published diets from 87 European studies to investigate patterns of resource use by four common deer species (moose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 63 publications
7
54
0
2
Order By: Relevance
“…This may explain why we found a relatively low tick burden on moose, which have particularly long legs [ 48 ]. Moreover, we found the highest infestation prevalence and intensity of nymphs on the ears of fallow deer, which supports our hypothesis that feeding type influences tick infestation rates, since fallow deer graze more than the other deer species [ 17 ]. Ticks, which are mostly questing on ground vegetation, will more easily access grazing ungulates via the ears (and the head) than species that more frequently browse vegetation strata higher up, such as moose [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…This may explain why we found a relatively low tick burden on moose, which have particularly long legs [ 48 ]. Moreover, we found the highest infestation prevalence and intensity of nymphs on the ears of fallow deer, which supports our hypothesis that feeding type influences tick infestation rates, since fallow deer graze more than the other deer species [ 17 ]. Ticks, which are mostly questing on ground vegetation, will more easily access grazing ungulates via the ears (and the head) than species that more frequently browse vegetation strata higher up, such as moose [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…We predict that (1) both roe deer and fallow deer show seasonal variation in nutrient composition of ingested forage, with more easily digestible forage (relatively high in nonstructural carbohydrates but low in digestible fiber and lignin) ingested in spring and summer compared to fall and winter because of the seasonal differences in availability of easily digestible forage (Van Soest 1994;Marshal et al 2005). In addition, we predict that (2) roe deer ingest forage higher in protein and nonstructural carbohydrates and lower in digestible fibers compared to fallow deer based on where these two ruminant species are placed on the continuum from browsers to grazers (Hofmann 1989), which is supported by findings by Spitzer et al (2020) and from the study area by Nichols et al (2016) who clearly show that fallow deer select grass to a much higher extent than roe deer. Grasses often contain higher concentrations of digestible fiber (both hemicellulose and cellulose) than herbs and browse (Hummel et al 2006;Verheyden-Tixier et al 2008).…”
Section: Introductionsupporting
confidence: 65%
“…Overall, cellulose and hemicellulose concentrations in rumen samples were positively correlated with each other. Roe deer in our study area are known to eat less graminoids compared to fallow deer (Nichols et al 2016), and other studies have shown that roe deer' intake of graminoids is low, ranging between 3.8% (winter) and ca 9% (growing season) (Cederlund et al 1980;Gębczyńska 1980;Obidziński et al 2013;Spitzer et al 2020). In contrast, there are several studies showing that the diet of fallow deer is frequently dominated by graminoids (e.g., Putman 1986;Poli et al 1996;Obidziński et al 2013;Nichols et al 2016), but sometimes it is dominated by trees or shrubs (Bruno and Apollonio 1991;Poli et al 1996) or acorns (Morse et al 2009).…”
Section: Discussionmentioning
confidence: 58%
“…Our model of habitat suitability suggested that fallow deer prefer flat areas with grassy vegetation types, probably because of a dietary preference for grasses (Elliott, Barrett 1985;Nugent 1990;Spitzer et al 2020). Flatter, open areas are also favourable for gregarious behaviour and sight-based anti-predator responses of ungulates (Hopewell et al 2005;Underwood 1982).…”
Section: Climate and Habitat Suitabilitymentioning
confidence: 99%
“…For covariate details, see Table S3. We expected that grassy vegetation types would positively influence fallow deer abundance (King, Forsyth 2020;Nugent 1990;Putman et al 1993;Spitzer et al 2020). We expected that highly rugged terrain would negatively affect deer abundance, and that alpine treeless vegetation -a low-productivity vegetation group occurring in harsh climates -might negatively affect deer abundance.…”
Section: (Iii) Fine-scale Habitat Suitabilitymentioning
confidence: 99%